2018
DOI: 10.1038/s42004-018-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Tuning artificial intelligence on the de novo design of natural-product-inspired retinoid X receptor modulators

Abstract: Instances of artificial intelligence equip medicinal chemistry with innovative tools for molecular design and lead discovery. Here we describe a deep recurrent neural network for de novo design of new chemical entities that are inspired by pharmacologically active natural products. Natural product characteristics are incorporated into a deep neural network that has been trained on synthetic low molecular weight compounds. This machine-learning model successfully generates readily synthesizable mimetics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 33 publications
0
115
0
5
Order By: Relevance
“…For computational de novo design of cell migration inducers we employed a pre‐trained RNN model that had successfully been used for generating bioactive new chemical entities in previous studies . This model was fine‐tuned by transfer‐learning using a collection of compounds exhibiting CXCR4 antagonistic activity in a variety of in vitro test systems with a potency threshold of <1 μM (“template” collection).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For computational de novo design of cell migration inducers we employed a pre‐trained RNN model that had successfully been used for generating bioactive new chemical entities in previous studies . This model was fine‐tuned by transfer‐learning using a collection of compounds exhibiting CXCR4 antagonistic activity in a variety of in vitro test systems with a potency threshold of <1 μM (“template” collection).…”
Section: Resultsmentioning
confidence: 99%
“…We previously applied an RNN with long short‐term memory cells (LSTM), which was trained with bioactive small molecules from ChEMBL, and by fine‐tuning with small sets of known bioactives (transfer learning), reoriented to generate target‐specific compounds. Prospective applications demonstrated that nuclear receptor modulators and natural‐product‐inspired bioactive molecules which were synthetically accessible and confirmed as having in vitro activity against the desired targets, could be obtained using this approach . Here, we apply this constructive machine learning approach to the computational design of cell migration modulators.…”
Section: Introductionmentioning
confidence: 99%
“…Merk, Schneider and coworkers validated the SMILES-LSTM transfer learning method 14 by generating compounds 1-3 for nuclear receptors, which after synthesis and testing showed micro-to nanomolar activity (see Figure 1). 66 Figure 1: Compounds 1-3, generated by a SMILES-LSTM model, 14 were made and tested, and showed micro-to nanomolar activity against the RXR and PPAR receptors. 66,67 An important result about the space that pretrained neural models can explore was recently published by Arus-Pous et al 68 They studied whether SMILES RNNs trained on a small subset (0.1%) of GDB13, an enumerated molecule set, which covers all potentially stable molecules up to 13 heavy atoms, could recover almost the full dataset after sampling a sufficient number of compounds.…”
Section: Models For De Novo Molecular Designmentioning
confidence: 99%
“…The process continues with the screening of the available databases for finding molecules that possess similar fingerprints to the generated ones. Generative models and deep neural networks (DLNs) have thus allowed generating molecules and promising candidates for useful drugs, basically from scratch, making it possible to "design perfect needles instead of searching for a needle in a haystack" (White and Wilson, 2010;Benjamin et al, 2017;Gómez-Bombarelli et al, 2018;Harel and Radinsky, 2018;Kang and Cho, 2018;Li et al, 2018b;Merk et al, 2018;Nouira et al, 2018;Popova et al, 2018;Sanchez-Lengeling and Aspuru-Guzik, 2018;Schneider, 2018).…”
Section: Co-occurring Machine-learning Contributions In Chemical Sciementioning
confidence: 99%